Assisted Living: “Acting Naturally” in Room 335 - Small, H (Athenaeum Press at Coastal Carolina University, 2014)
Documentary film and television have played, and continue to play, a major role in shaping public conversations about standards of care today for those in later life who are no longer able to live independently. The starkest example in the UK in recent years was the BBC Panorama documentary Undercover Care: The Abuse Exposed, aired in May 2011, which contributed heavily to official denunciation of the Care Quality Commission as “unfit for purpose.” This paper looks in detail at a less gruelling example of the genre. Neither an exposé of malpractice nor a fly-on-wall documentary, Room 335 (HBO Documentary Films, 2006) is closer to participant anthropology—though it is not quite that either. The paper, delivered as a plenary lecture to the British Society of Gerontology Annual Conference, September 2013, makes a case for valuing the quality of the film’s improvisational, non-“findings driven” engagement with its subjects, and the light it sheds on the nature and significance of friendship in old age. The film can be downloaded from Apple iTunes at https://itunes.apple.com/ca/artist/andrew-jenks/id563448630.